2016
DOI: 10.1093/hmg/ddw289
|View full text |Cite
|
Sign up to set email alerts
|

Targeted sequencing of genome wide significant loci associated with bone mineral density (BMD) reveals significant novel and rare variants: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study

Abstract: Background Bone mineral density (BMD) is a heritable phenotype that predicts fracture risk. We performed fine-mapping by targeted sequencing at WLS, MEF2C, ARHGAP1/F2 and JAG1 loci prioritized by eQTL and bioinformatic approaches among 56 BMD loci from our previous GWAS meta-analysis. Methods and Results Targeted sequencing was conducted in 1,291 Caucasians from the Framingham Heart Study (n = 925) and Cardiovascular Health Study (n = 366), including 206 women and men with extreme low femoral neck (FN) BMD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Mef2c ’s role in multiple cell types has been well studied [ 12 , 13 ]. SNPs associated with the Mef2c locus are associated with osteoporosis and osteoporotic fractures [ 14 , 15 , 16 ]. Mef2c has been shown to regulate chondrocytes and osteoblast differentiation in mouse models [ 17 ]; however, its role in osteoclast differentiation has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Mef2c ’s role in multiple cell types has been well studied [ 12 , 13 ]. SNPs associated with the Mef2c locus are associated with osteoporosis and osteoporotic fractures [ 14 , 15 , 16 ]. Mef2c has been shown to regulate chondrocytes and osteoblast differentiation in mouse models [ 17 ]; however, its role in osteoclast differentiation has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, genome-wide association studies (GWAS) have identified more than 65 novel genomewide significant loci for BMD and detected 14 risk loci for fracture (Estrada et al, 2012). In a targeted sequencing of genome-wide significant loci for BMD, WLS, ARHGAP1, and 5′ of MEF2C were identified much more strongly associated with BMD compared to the GWAS SNPs (Hsu et al, 2016). However, the full genetic mechanism of BMD remains elusive now.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous sequencing studies of candidate genes in GWAS loci identified rare large-effect variants 20 22 . To assess the potential contribution of rare variants at the chromosome 6q24.1 locus to AIS, we carried out targeted sequencing.…”
Section: Resultsmentioning
confidence: 99%